DOI: 10.33915/etd.307
|View full text |Cite
|
Sign up to set email alerts
|

Development of hydrogel tracer beads and comparative tracer tests to better understand contaminant fate and transport in karst systems

Abstract: Development of hydrogel tracer beads and comparative tracer tests to better understand contaminant fate and transport in karst systems Amanda Laskoskie Karst aquifers can be highly susceptible to contamination due to a close connection to the land surface, lack of filtration through a soil zone, and rapid transmission along solutionallyenhanced flowpaths. These factors also allow for aquifer contamination by direct injection of immiscible organic compounds in the form of non-aqueous phase liquids (NAPLs). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…The tracer tests were conducted in the laboratory (Experimental Stream Facility) as well as in the field (Buckeye Creek Cave). In both of these sites, the systems have an air-water interface, but other than that, the sites are not directly comparable to Even with all of the differences between both sites, Laskoskie (2013) found that the buoyant HTBs traveled faster than the solute tracer.…”
Section: Comparative Tracer Tests With Htbsmentioning
confidence: 93%
See 4 more Smart Citations
“…The tracer tests were conducted in the laboratory (Experimental Stream Facility) as well as in the field (Buckeye Creek Cave). In both of these sites, the systems have an air-water interface, but other than that, the sites are not directly comparable to Even with all of the differences between both sites, Laskoskie (2013) found that the buoyant HTBs traveled faster than the solute tracer.…”
Section: Comparative Tracer Tests With Htbsmentioning
confidence: 93%
“…Since density plays a critical role on the movement of NAPLs, the transport of commonly used dissolved tracers such as fluorescent dyes and salts or non-dissolved tracers such as microspheres is not applicable to that of NAPLs. Therefore, in order to better predict the behavior of NAPLs, Laskoskie (2013) developed a particle tracer named hydrogel tracer beads (HTBs). These are millimetersized particles formed by cross-linked sodium alginate polymers that can be made with different fluorescent pigments and density-modifying additives.…”
Section: Statement Of Purposementioning
confidence: 99%
See 3 more Smart Citations